STRATIFIKASI SOSIAL DALAM ROMAN â€œREICH UND ARMâ€ KARYA FRANZ MICHAEL FELDER - AFRYSNA, TERESIA (IDENTITAET, 2016)
Conclusion: Novel, Social Stratification The background of this study is the interest of researcher to the social stratification in the novel Reich und Arm of Franz Michael Felder. The object of this study is novel Reich und Arm of Franz Michael Felder. The problems in this research are: 1) Overview of social stratification whether urban Bregenzerwald in roman Reich und Arm of Franz Michael Felder? 2) The impact of social stratification what happens to the characters? This study is a qualitative descriptive. The data in this study is sentence about the social stratification issues contained in the novel Reich und Arm of Franz Michael Felder. The results of this study has Een overview the city community Bregenzerwald in status based, Gender, Education,Jobs, Economy. As for the impact of their social stratification that there are positive or negative. The positive is their willingness to work hard to change the fate for the better, and  negative impact is form of completion, of contravention and conflict.